2019
DOI: 10.1109/access.2019.2901801
|View full text |Cite
|
Sign up to set email alerts
|

Is DNS Ready for Ubiquitous Internet of Things?

Abstract: The vision of the Internet of Things (IoT) covers not only the well-regulated processes of specific applications in different areas but also includes ubiquitous connectivity of more generic objects (or things and devices) in the physical world and the related information in the virtual world. For example, a typical IoT application, such as a smart city, includes smarter urban transport networks, upgraded water supply, and waste-disposal facilities, along with more efficient ways to light and heat buildings. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…It mainly focuses on functionality, security, and availability problems. The work in [147] investigates whether the current DNS is ready for IoT. The authors lay out criteria that should be met before using DNS with IoT and analyze whether these criteria are met or not.…”
Section: Impact Of Iot On Dnsmentioning
confidence: 99%
“…It mainly focuses on functionality, security, and availability problems. The work in [147] investigates whether the current DNS is ready for IoT. The authors lay out criteria that should be met before using DNS with IoT and analyze whether these criteria are met or not.…”
Section: Impact Of Iot On Dnsmentioning
confidence: 99%
“…Siljanovski et al demonstrated the feasibility of successfully implemented mDNS/DNS-SD on embedded systems (ATMega1284p, 8 MHz, 128 KB flash, and 16 KB RAM) [7]. Despite its high compatibility and widespread use, mDNS/DNS-SD suffers from a lack of explicit guidelines concerning endpoint communication behavior, leading to considerable performance variances across different implementations [8]. As a result, much of the existing research aims to enhance efficiency and reduce network traffic.…”
Section: Related Workmentioning
confidence: 99%
“…These advancements render our proposed approach compatible with two of the most widely adopted low-power and lossy network (LLN) standards in the IoT landscape. In application-specific domains, research has explored the use of mDNS/DNS-SD in intelligent transportation systems (ITS) [8], smart cities [13], and microservices management [14].…”
Section: Related Workmentioning
confidence: 99%
“…When the application process needs to map a host domain name to an IP address, the domain name resolution function is called, and the resolution function puts the converted domain name in the DNS request and sends it to the local domain name server via UDP message [32]. After the local domain name server searches the domain name, it returns the corresponding IP address in the reply message.…”
Section: B Construction Of Domain Name Whitelist Substring Setmentioning
confidence: 99%